Lost empire [large type] - Cussler, Clive (Cussler, Clive. Fargo adventures., 2010)
Through Tanzania and Zanzibar, into the rainforests of Madagascar, and across the Indian Ocean to Indonesia and the legendary site of the 1883 Krakatoa explosion, husband-and-wife treasure-hunting team Sam and Remi Fargo and their ruthless opponents pursue the hunt for a relic--but only one can win. And the penalty for failure is death.